MAKNA FILOSOFIS UPACARA SEREN TAUN DUSUN PAGERBATU DESA BATULAWANG KECAMATAN PATARUMAN KOTA BANJAR - Cika Amelia Raka Fasa; Yadi Kusmayadi; Dewi Ratih (Faculty of Teacher Training and Education, 2026)
The Seren Taun ritual has long been recognized as one of the most enduring agrarian ceremonial traditions within Sundanese cultural communities. However, existing studies predominantly focus on its function as a harvest thanksgiving ritual and cultural preservation practice, while limited attention has been paid to the localized philosophical reinterpretation of the ritual within contemporary Islamic Sundanese communities. This study examines the symbolic meanings embedded in the Seren Taun ritual practiced in Pagerbatu Hamlet, Batulawang Village, Pataruman District, Banjar City, with particular emphasis on the negotiation between Sundanese agrarian cosmology and Islamic spirituality. Employing an interpretive ethnographic approach, data were collected through participant observation, semi-structured interviews with seven key informants, and documentation. Data were analyzed using thematic coding and interpreted through the perspectives of symbolic anthropology and ritual theory. The findings reveal that Seren Taun in Pagerbatu functions not merely as an agrarian thanksgiving ceremony but as a symbolic arena where spiritual purification, ecological ethics, social solidarity, and localized Islamic religiosity are continuously reproduced. The ritual demonstrates a dynamic cultural negotiation in which ancestral cosmological values are reinterpreted within Islamic theological frameworks without eliminating their local symbolic structures. This study contributes to discussions on cultural resilience by demonstrating how local ritual traditions adapt to modern religious and social transformations while maintaining their philosophical integrity.